Technical research of detection algorithmically generated malicious domain names using machine learning methods - Ho, Hieu Duc; Ho, Huong Van (Journal of Science and Technology on Information security, 2020)
Abstract— In recent years, many malware use domain generation algorithm for generating a large of domains to maintain their Command and Control (C&C) network infrastructure. In this paper, we present an approach for detecting malicious domain names using machine learning methods. This approach is using Viterbi algorithm and dictionary for constructing feature of domain names. The approach is demonstrated using a range of legitimate domains and a number of malicious algorithmically generated domain names. The numerical results show the efficiency of this method. Tóm tắt— Trong những năm gần đây, nhiều phần mềm độc hại sử dụng thuật toán sinh tên miền tạo ra lượng lớn các tên miền để duy trì cơ sở hạ tầng mạng ra lệnh và điều khiển (C&C). Trong bài báo này, chúng tôi trình bày một cách tiếp cận để phát hiện tên miền độc hại bằng phương pháp học máy. Cách tiếp cận này sử dụng thuật toán Viterbi và tập từ điển để trích xuất các đặc trưng của tên miền. Cách tiếp cận được thể hiện bằng cách sử dụng một lượng lớn các tên miền hợp pháp và một lượng lớn tên miền độc hại được tạo ra bằng thuật toán sinh tên miền. Các kết quả thực nghiệm đã chỉ ra tính hiệu quả của phương pháp.